Analysis of the MX/G/1 queue under D-policy - Lee, Ho Wee (2013)
We study the queue length of the MX /G/1 queue under D-policy. We derive the queue length PGF at an arbitrary point of time. Then, we derive the mean queue length. As special cases, M/G/1, MX /M/1, and M/M/1 queue under D-policy are investigated. Finally, the effects of employing D-policy are discussed.